Stakeholders’ Consultation Meeting on Agrifood value chains in Odisha – Challenges and Opportunities - Bhattacharjee, Suchiradipta; Breisinger, Clemens; Kassim, Yumna; Pauw, Karl (CGIAR System Organization, 2023)
Odisha’s rural economy is reshaping because of urbanization, market expansion, increased livelihood opportunities in the non-farm sector and changes in land use patterns. Economic and institutional reforms are underway, and their successful implementation in the next few years will increase the per capita income and improve the average living standard of the people.